PENERIMAAN AUDITOR TERHADAP UNDER-REPORTING TIME - Ceacilia Srimindarti; Elen Puspitasari (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2013)
This study seeks to analyze the relationship between the factors that affect the auditor’s acceptanceof under-reporting time. Auditor’s who worked in Public Accounting in Indonesia is an object in this studyusing questionnaire-based survey that was sent. The data have been collected and analyzed using SPSS.Expectancy theory and the theory of goal setting is the basic theory used to explain the behavior of auditorsunderreporting time in accepting. The results of this study found that locus of control variables have a positiveand signifi cant impact on acceptance of under-reporting time, while the variable of organizational commitmentauditor has no infl uence on the acceptance of under-reporting time. Adversely affect the auditor’s expertiseacceptance under-reporting time. These results indicate that the internal factors affecting the acceptance ofindividual auditor’s under-reporting time.Keywords: locus of control, auditor’s expertise, organizational commitment, acceptance of under-reportingtime, expectancy theory and the theory of goal setting.